Novelty and Creativity. - Gilliland, Rex (2009)
Keywords: dept.phi; faculty_collection

Writing Two Major Chapters of a Book on Flourishing Ethics: Sabbatical Spring 2009 - Bynum, Terrell Ward (2009)
The chapter on the information ethics of Oxford scholar, Luciano Floridi, was completed and is scheduled for publication in Floridi's anthology. The keynote address, Philosophy and the Information Revolution, presented at the Computer Ethics: Philosophical Enquiry 2009 conference in Corfu, Greece, is also scheduled for publication in the journal Ethics and Information Technology. The ideas from both articles have been included in the curriculum for the Computer Ethics class at SCSU.
Keywords: dept.phi; faculty_collection

Response to Frisina's response - Yang, X. (Dao, 2009)
0 citations (Crossref) [2023-10-31]
Keywords: dept.phi; peer-reviewed

Milestones in the History of Information and Computer Ethics - Bynum, Terrell Ward (The Handbook of Information and Computer Ethics, 2009)
This chapter contains sections titled: Introduction Norbert Wiener's Foundation of Information Ethics Computer Ethics Developments after Wiener and before Maner Walter Maner's Computer Ethics Initiative Deborah Johnson's Influential Textbook and the Start of the “Uniqueness Debate” James Moor's Classic Paper and His Influential Computer Ethics Theory The Professional-Ethics Approach of Donald Gotterbarn Computing and Human Values Luciano Floridi's Information Ethics Theory Concluding Remarks: The Exponential Growth of Computer Ethics References and Selected Resources
Keywords: Computer ethics developments - after Wiener and before Maner; Donald Gotterbarn professional-ethics approach; Information and computer ethics - milestones in history; computer ethics developments - after Wiener and before Maner; dept.phi; information and computer ethics - milestones in history

Federative Global Democracy - Cavallero, Eric (Metaphilosophy, 2009)
Abstract: In this essay a set of principles is defended that yields a determinate allocation of sovereign competences across a global system of territorially nested jurisdictions. All local sovereign competences are constrained by a universal, justiciable human rights regime that also incorporates a conception of cross-border distributive justice and regulates the competence to control immigration for a given territory. Subject to human rights constraints, sovereign competences are allocated according to a conception of global democracy. The proposed allocation scheme can accommodate substantial local autonomy while at the same time ensuring that everyone has a voice in the political decisions that affect his or her interests. The relevant class of affected interests is fully specified. Relevant affects are of two kinds: those that impose norms of governance on individuals, and those that impose external costs on them. The favored sense of “an external cost” is developed and defended.
9 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/151-680-891-324-807, pop00258 tex.type: [object Object]
Keywords: Affected interests; All-affected principle; Borders; Confederalism; Democracy; Democratic deficit; Equal protection; External costs; Externalities; Federalism; Global governance; Global justice; Globalization; Human rights; Immigration; International law; affected interests; all-affected principle; borders; confederalism; democracy; democratic deficit; dept.phi; equal protection; external costs; externalities; federalism; global governance; global justice; globalization; human rights; immigration; international law; nationalism; sovereignty; territoriality

How to make sense of the claim “True knowledge is what constitutes action”: A new interpretation of wang yangming’s doctrine of unity of knowledge and action - Yang, Xiaomei (Dao-a Journal of Comparative Philosophy, 2009)
No one denies the importance of applying knowledge to actions. But claiming identity (unity) of knowledge and action is quite another thing. There seem to be two problems with the claim: (1) the identity claim implies that the sole cause for one to fail to act on what one judges to be right is ignorance, but it is obviously false that the sole cause of failure in moral actions is ignorance. (2) The identity statement implies non-separation of knowledge and action. But knowledge does not necessarily lead to action. However, the identity of knowledge and action is what a famous Ming Confucian scholar, Wang Yang-ming, proposed and the concept became the central doctrine of his teaching. Though there are several major interpretations of Wang's doctrine in contemporary literature, it is not clear to me how they deal with the above mentioned difficulties. In this article, I will discuss these interpretations of the doctrine and propose a new interpretation. My purpose is to give an interpretation of Wang's doctrine that has the capacity of dealing with these challenges to the doctrine and also captures the essence of his teaching. © 2009 Springer Science+Business Media B.V.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/070-501-215-892-486 tex.type: [object Object]
Keywords: Action; Chinese philosophy; Moral knowledge (liang zhi); Neo-confucianism; dept.phi; peer-reviewed